2017
DOI: 10.1016/j.jpba.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the antimalarial drug pyronaridine in whole blood using LC–MS/MS — Increased sensitivity resulting from reduced non-specific binding

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Pyronaridine has been shown to have an extended half-life in humans, with a half-life elimination in whole blood of approximately 17 d [84] and 33.5 d for the total radioactive half-life [85] which compares favorably with our observations in mice in this study (Fig 3). A mass balance study in healthy volunteers indicated nine primary and four secondary metabolites of pyronaridine [85] and recombinant CYP studies suggested that these metabolites were generated by cytochrome P450s CYP1A2, CYP2D6, and CYP3A4 [31].…”
Section: Discussionsupporting
confidence: 87%
“…Pyronaridine has been shown to have an extended half-life in humans, with a half-life elimination in whole blood of approximately 17 d [84] and 33.5 d for the total radioactive half-life [85] which compares favorably with our observations in mice in this study (Fig 3). A mass balance study in healthy volunteers indicated nine primary and four secondary metabolites of pyronaridine [85] and recombinant CYP studies suggested that these metabolites were generated by cytochrome P450s CYP1A2, CYP2D6, and CYP3A4 [31].…”
Section: Discussionsupporting
confidence: 87%
“…Besides, SPE has the best clean-up efficiency but is time consuming, which often serves as the last option when both PPT and LLE fell flat (Blessborn et al, 2017;Koller, Zubiaur, Saiz-Rodriguez, Abad-Santos, & Wojnicz, 2019;Montesano et al, 2017). Occasionally, researchers may choose to combine two of these methods.…”
Section: Conventional Pretreatment Methodsmentioning
confidence: 99%
“…[34] PYR is a fast-acting drug and it has a long biological half-life (13-17 days). [35] It is a useful molecule to delay the recrudescence of parasites and appearance of multidrug-resistance. Thus far, no case of drug-resistance induced by PYR has been observed.…”
Section: Pyronaridine As An Antimalarial Drugmentioning
confidence: 99%